The Integrated Marketing Communication Strategy to Increase the Number of Students at Madrasah Tsanawiyah Muhammadiyah Gedongtengen Using Digital Platforms - Isninda Nur Hanifa Arisetia; Muhammad Najih Farihanto (Jogjakarta Communication Conference (JCC), 2024)
This research focuses on the problem of marketing communication strategies carried out by Madrasah Tsanawiyah Muhammadiyah Gedongtengen in increasing the number of students. This madrasah has a limited number of students, and in the last four years, it has been proven that the number of students has decreased. The method used in this research is a qualitative descriptive method, and data collection techniques are carried out by researchers through interviews, documentation, and observation. Madrasah Tsanawiyah Muhammadiyah Gedongtengen implements a direct marketing strategy and conducts promotions through several digital platforms. Factors influencing the increase in student numbers are the promotion of discounts on school fees and the use of digital platforms. The research results show that Madrasah Tsanawiyah Muhammadiyah Gedongtengen uses all elements of the Integrated Marketing Communication theory to increase the number of students. In conclusion, the most effective strategy is word-of-mouth marketing, and promotions are carried out on several digital platforms.